The Life in Inventions: Patents as Sources of Biological Information - Gary Mason Church; Brian B. Carpenter (Issues in Science and Technology Librarianship)
Scientific conference papers have traditionally been a relatively quick and important source of information for the biologist. These papers are also a vital part of the scientific process and a way to spread, evaluate, and refine scientific knowledge. Information from conference papers can be supplemented with information from patents. Patent information comprises an important part of the biological literature, especially that dealing with biotechnology and genomics. For a variety of reasons, however, biologists do not generally consult information in patents relevant to their interests.